PVA-BA/PEG hydrogel with bilayer structure for biomimetic articular cartilage and investigation of its biotribological and mechanical properties - Cui, Lingling; Tong, Wei; Zhou, Huangjie; Yan, Chengqi; Chen, Junyue; Xiong, Dangsheng (Journal of materials science, 2021)
Polyvinyl alcohol (PVA) is perceived as a candidate of synthetic articular cartilage, whose real-world applications have been hindered by poor mechanical and biotribological properties. One-step gelation method was used herein for the synthesis of a biomimetic PVA-BA/PEG hydrogel with porous bilayer structure. Importantly, two layers were integrated closely and both showed porous network. The upper layer of this hydrogel could show high compressive tangent modulus to resist deformation during friction; in the meantime, its bottom layer was able to prevent the leakage of interstitial water and increase the consumption of load. Due to porous high-water-content hydrogel bulk inside bottom layer, this cast-dry PVA-BA/PEG hydrogel could show close to 70% of water-retention capacity. On the other hand, the complexation of BA and PVA greatly strengthened the stability of the polymer network for the PVA-BA/PEG hydrogel. Therefore, the PVA-BA/PEG hydrogel could achieve an excellent combination of high mechanical properties and low friction coefficient. When the addition of BA was 1.4 wt %, the tensile strength of the PVA-BA/PEG hydrogel reached 4.41 MPa at an elongation of 573% and its compressive tangent modulus was 4.6 MPa at a strain of 60%. The COF of the hydrogel under water lubrication or calf serum was very low even at a high load, which is of high application potential for the articular cartilage repair.